Asuhan Keperawatan Pada Tn.S dan Tn.A Dengan Diabetes Mellitus Diruang Penyakit Dalam Di RSU Kota Tangerang Selatan - Muhamad Ridlo (Politeknik Karya Husada, 2022)
Background: Background: Diabetes mellitus is one of the problems in the world which is currently increasing due to unstable blood sugar levels caused by damage to insulin secretion, insulin action or both. Objective: To obtain an overview and be able to perform nursing care in patients with Diabetes Mellitus. Methods: The research design in this case uses descriptive analytic by using a case study approach whose sample consists of two patients, namely Mr. S and Mr. A based on medical surgical nursing care. Results: After nursing care for 3 X 24 hours on Mr. The results show that chronic pain has been resolved because the pain scale has decreased to 1, the instability of blood glucose levels is partially resolved because the GDS results are still high, the risk of infection is resolved in part because there is still redness in the wound, impaired physical mobility is partially resolved because the patient still has difficulty moving. While at Mr. A, after nursing care for 3 x 24 hours, all results were resolved on 3 diagnoses, namely unstable blood glucose levels, nausea, sleep pattern disturbances because there were significant changes. Conclusion: Based on the results above, that people with diabetes mellitus who experience increased blood sugar levels caused by non-adherence to diet and non-adherence in treatment, it is necessary for nurses to play a role in providing health education by advocating healthy food and teaching self-care. Keywords: Case Study, Diabetes Mellitus, Nursing Care, unstable blood glucose level